2003
DOI: 10.1007/s00221-003-1589-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of the medial parieto-occipital cortex in the control of reaching and grasping movements

Abstract: The medial parieto-occipital cortex is a central node in the dorsomedial visual stream. Recent physiological studies in the macaque monkey have demonstrated that the medial parieto-occipital cortex contains two areas, the visual area V6 and the visuomotor area V6A. Area V6 is a retinotopically organized visual area that receives form and motion information directly from V1 and is heavily connected with the other areas of the dorsal visual stream, including V6A. Area V6A is a bimodal visual/somatosensory area t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
182
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 279 publications
(217 citation statements)
references
References 67 publications
33
182
2
Order By: Relevance
“…Finally, our results are perfectly consistent with the theory of a dorsomedial visual stream involved in reach‐to‐grasp actions, suggested by Galletti et al. (2003) in nonhuman primates, and well documented by Fattori et al. (2009, 2010).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Finally, our results are perfectly consistent with the theory of a dorsomedial visual stream involved in reach‐to‐grasp actions, suggested by Galletti et al. (2003) in nonhuman primates, and well documented by Fattori et al. (2009, 2010).…”
Section: Resultssupporting
confidence: 65%
“…These recent findings in humans are consistent with the theory of a dorsomedial visual stream (e.g., V6A) involved in reach‐to‐grasp actions, suggested by Galletti et al. (2003). Indeed, this has been documented by Fattori et al.…”
Section: Introductionmentioning
confidence: 99%
“…These functions are anatomically segregated into specific subregions of the PPC. Medial areas, such as the medial intraparietal area and the "parietal reach region," are engaged by reaching to cued targets in the workspace (21)(22)(23)(24)(25)(26); lateral cortical regions surrounding the intraparietal sulcus (area 5 and the anterior interparietal area) signal the hand postures used to grasp specific objects (27)(28)(29)(30)(31); and areas of the medial wall of the hemisphere integrate arm and hand movements with visual signals (32,33). Motor plans and sensory attention are transformed into action by parietal interconnections with relevant premotor areas of the frontal lobe.…”
Section: I Ii I I I I Ii I I I I I I I I I I I I I I I I I I I I I mentioning
confidence: 99%
“…While the "two streams" model remains a touchstone for the interpretation and integration of clinical, physiological, and anatomical data on visual processing, it continues to evolve. For example, several studies have suggested that the primate dorsal stream is, itself, formed by distinct dorsolateral and dorsomedial circuits, which mediate different aspects of visual behavior (Rosa and Tweedale, 2001;Galletti et al, 2003;Rizzolatti and Matelli, 2003). Perhaps reflecting this dual organization, anatomical studies have demonstrated parallel projections from the primary visual area (V1) to two heavily myelinated, motion-sensitive dorsal areas, which in turn project to the posterior parietal cortex.…”
Section: Introductionmentioning
confidence: 99%